Emerging roles of i-motif in gene expression and disease treatment - Luo, Xiaoqing; Zhang, Jianye; Gao, Yue; Pan, Weifei; Yang, Yayuan; Li, Xu; Chen, Lingfei; Wang, Chang; Wang, Yuqing (Frontiers in Pharmacology, 2023)
As non-canonical nucleic acid secondary structures consisting of cytosine-rich nucleic acids, i-motifs can form under certain conditions. Several i-motif sequences have been identified in the human genome and play important roles in biological regulatory functions. Due to their physicochemical properties, these i-motif structures have attracted attention and are new targets for drug development. Herein, we reviewed the characteristics and mechanisms of i-motifs located in gene promoters (including c-myc, Bcl-2, VEGF, and telomeres), summarized various small molecule ligands that interact with them, and the possible binding modes between ligands and i-motifs, and described their effects on gene expression. Furthermore, we discussed diseases closely associated with i-motifs. Among these, cancer is closely associated with i-motifs since i-motifs can form in some regions of most oncogenes. Finally, we introduced recent advances in the applications of i-motifs in multiple areas.